Improving the cancer adult patient support network (iCAN): a pilot study on a communication model and modified focus group - Campisi, Giuseppina; Bazzano, Monica; Mauceri, Rodolfo; Panzarella, Vera; La Mantia, Gaetano; Di Fede, Olga (Frontiers in Psychology, 2023)
Background Many consider that cancer has the greatest impact of any disease in the world, and it can drastically limit patients’ quality of life. Combating such a life-threatening disease can pose many challenges to daily life, highlighted by demonstrating the need to discuss one’s health status within a focus group and encourage treatment compliance. Aim the purposes of this study were to share the authors’ experience of a modified focus group in an Oral Medicine Unit, termed “Improving Cancer Adult Patients Support Network” (iCAN), and to evaluate how effective communication could improve patients’ quality of life and empower them by virtue of enhanced knowledge and an awareness of cancer management. Methods the paper adhered to the COREQ checklist regarding its reporting procedures. The iCAN format was precisely reproduced four times with four groups, consisting of 12 adult male and female patients with solid cancers. They discussed several main topics relating to cancer treatment, as chosen by a majority of the participants. Four specialists were involved in the discussion of the selected topics The iCAN format was faithfully reproduced during each meeting, with the participants in the roles of moderator and health specialists. Finally, a satisfaction questionnaire was administered. Results the most reliable results demonstrated a marked change in lifestyle and eating habits in more than 50% of participants. More than 80% were unaware of the side effects of cancer treatments in general and the oral mucosa in particular. Each meeting reported a maximum degree of satisfaction experienced by the participants. Conclusion iCAN focus group meetings appear to have facilitated a process of narrative interviewing, thereby improving the doctor-patient relationship underlying the humanization of the care process.